2020
DOI: 10.1038/s41467-020-17709-0
|View full text |Cite
|
Sign up to set email alerts
|

Dead cells release a ‘necrosignal’ that activates antibiotic survival pathways in bacterial swarms

Abstract: Swarming is a form of collective bacterial motion enabled by flagella on the surface of semisolid media. Swarming populations exhibit non-genetic or adaptive resistance to antibiotics, despite sustaining considerable cell death. Here, we show that antibiotic-induced death of a sub-population benefits the swarm by enhancing adaptive resistance in the surviving cells. Killed cells release a resistance-enhancing factor that we identify as AcrA, a periplasmic component of RND efflux pumps. The released AcrA intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 94 publications
(133 reference statements)
5
61
0
Order By: Relevance
“…Thus, significant substitutions in the sequences may lead to the loss of important functions in cell physiology of E. coli bacteria. This observation was confirmed in a recent work (Bhattacharyya et al, 2020 ), which demonstrated the key role of individual amino acid residues of AcrA and TolC in “necrosignal” recognition that activates swarm-specific resistance in an E. coli population. Thus, it can be assumed that the AcrAB-TolC pump may not only remove certain molecules from the cell, but also is a keystone element in regulatory processes important for the physiology of bacteria.…”
Section: All Escherichia Coli Strains Demonstratedsupporting
confidence: 69%
“…Thus, significant substitutions in the sequences may lead to the loss of important functions in cell physiology of E. coli bacteria. This observation was confirmed in a recent work (Bhattacharyya et al, 2020 ), which demonstrated the key role of individual amino acid residues of AcrA and TolC in “necrosignal” recognition that activates swarm-specific resistance in an E. coli population. Thus, it can be assumed that the AcrAB-TolC pump may not only remove certain molecules from the cell, but also is a keystone element in regulatory processes important for the physiology of bacteria.…”
Section: All Escherichia Coli Strains Demonstratedsupporting
confidence: 69%
“…Swarming bacteria can also collectively tolerate antibiotic treatments that are lethal to planktonic cells – albeit only to a lesser degree than biofilms – through motility-induced mixing and reduced small-molecule absorption ( Bhattacharyya et al, 2020 ; Butler et al, 2010 ; Lai et al, 2009 ). As a rapid mode of surface colonization ( Kearns, 2010 ), a swarm’s ability to withstand high antibiotic concentrations could therefore lead to the subsequent establishment of highly resilient biofilms in regions that could not have been reached otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…The increased ethidium bromide accumulation represents a net increase in uptake and could be explained by alterations to the rate of influx, efflux, or both. To differentiate these possibilities, we quantified influx kinetics using resazurin-based PrestoBlue, a dye that becomes fluorescent after import into the cytosol 46 . In planktonic cells we observe a small, but statistically significant increase in the rate of dye influx in ∆ cydAB relative to wild-type (slope: 2.6 and 3.0 for wild-type and ∆ cydAB , respectively) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of PrestoBlue (Invitrogen) was performed as previously described 46 . Planktonic cultures were grown to mid-logarithmic phase and normalized to OD 600 = 1.0 in PBS.…”
Section: Methodsmentioning
confidence: 99%